Αρχές οργάνωσης και διοίκησης επιχειρήσεων: μια εμπειρική προσέγγιση στην εκπαίδευση - Μπρίνια Βασιλική (SPOUDAI Journal of Economics and Business, 2007)
Theoretically, the application of the Project method can take place in any school environment and in the frame of each school rank, but only when certain basic conditions are filled. In practice and particularly in the frame of Greek educational system, the things are more complicated, because, as long as we advance from the most inferior to the most superior ranks, the application possibilities of method are dissolved, because of the application of Timetable and Analytic Schedule, that do not allow initiatives and innovatory opinions. According to our opinion, theoretically, the rank of High School is advisable particularly for the teaching of courses with the Project method, because on the other hand, the developmental phase, in which the students of high school find themselves, offers more pledges for a more faithful attendance of students in processes as e.g. the experiential-communicative training process, that require bigger autonomy of action, on the other hand, the introduction of this method and the type of teaching and learning that it represents can be particularly sub-auxiliary to the direction of the constitution of the personality of tomorrow’s academic citizen, serving thus preparation needs for the Higher education. The paradox for this case constitutes the fact that in Greek school reality the structure and the organisation of life of the high school is at such way strictly predestined so as each removal attempt from the specifications is considered particularly bold and rather impossible. The Greek high school is compelled to negotiate, in regular time frames, specific quantities of knowledge and to achieve specific objectives. This fact, by its own, constitutes characteristic deterrent for initiatives and innovatory applications. Nevertheless, everyone could think that also the school models leave always some windows of freedom, which if the teacher rightly develops them, we can experience some «inversions».